(untitled) - Lindsay N Childs (New York, 1995)
This book is an informal and readable introduction to higher algebra at the post-calculus level. The concept of ring and field are introduced through study of the familiar examples of the intergers and polymials. A strong emphasis on congruence classes leads in a natural way to finite groups and finite fields. The new examples and theory are built in a well-motivated fashion and made relevant by many applications - to crytography, coding, integration, history of mathematics, and especially to elementary and computational number theory. The book includes expositions of Rabin's probabilistic primality test, quadratic reciprocity, and the classification of finite fields
Keywords: algebra